Mandatory ECG screening of athletes: Is this question now resolved? - Shephard, R. J. (Sports Medicine, 2011)
European and North American cardiologists have long debated the need for mandatory ECG screening of athletes in order to prevent sudden cardiac death. European investigators have recently adduced new evidence, which they believe supports the need for such screening. They note a decrease of sudden cardiac deaths among Italian athletes following the introduction of mandatory screening in that country, clearer definitions of resting ECG abnormalities in athletes, new and more encouraging calculations of cost/benefit ratios and direct comparisons of clinical examination alone against clinical examination plus ECG screening. Nevertheless, it seems that critical criteria for the success of any screening procedure (a substantial prevalence of the problem, coupled with an adequate test sensitivity and specificity) have yet to be satisfied. Very few athletes are liable to sudden cardiac death, only a few of those who are vulnerable will be identified by ECG screening, and even if all potential cases could be detected, restriction of their physical activity would be unlikely to have a major influence on their prognosis. At the same time, a requirement of mandatory testing would discourage engagement in physical activity, and would impose substantial direct costs on the community. Moreover, the large number of false positive test results could have important and undesirable consequences for both indirect medical costs and the overall health of competitors. ECG screening might become more effective if it could be focused on a smaller sub-group of vulnerable athletes, or if the problem of false positive tests could be addressed through an increase of test specificity. However, on the basis of current information, it would seem better to direct efforts in preventive medicine to more common causes of premature death in the young adult.